Implementation Income Tax 23 On Logistics Services At Pt. Prima Indonesia Logistics In 2022 - Nurlela; Laelisneni; Nst, Lily Karlina; Tampubolon, Mayshin Meriana (CV. Utility Project Solution, 2023)
This study aims to determine the application of withholding and reporting income tax article 23 on logistics services at PT Prima Indonesia logistics. The types and sources of data obtained are secondary data where the data presented has been collected previously from the company's internal parties in the form of income recaps, proof of deductions and time tax returns. Data collection techniques are carried out by means of interviews, documentation and literature studies. The data analysis method uses quantitative descriptive methods. The results of this study show that PT. Prima Indonesia logistics has implemented calculations, and withheld article 23 income tax at a rate of 2% in accordance with Minister of Finance Regulation Number 141/PMK.03/2015. PT. Prima Indonesia logistics has deposited and reported Article 23 Income Tax in accordance with the provisions contained in the Regulation of the Director General of Taxes Number Per – 24 / PJ / 2021 amending the Regulation of the Director General of Taxes Number Per- 23 / PJ / 2020.